2005
DOI: 10.1523/jneurosci.5027-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward Inhibition of Projection Neurons by Fast-Spiking GABA Interneurons in the Rat StriatumIn Vivo

Abstract: Discharge activities and local field potentials were recorded in the orofacial motor cortex and in the corresponding rostrolateral striatum of urethane-anesthetized rats. Striatal projection neurons were identified by antidromic activation and fast-spiking GABAergic interneurons (FSIs) by their unique characteristics: briefer spike and burst responses. Juxtacellular injection of neurobiotin combined with parvalbumin immunohistochemistry validated this identification. Spontaneous activities and spike responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
396
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(434 citation statements)
references
References 50 publications
38
396
0
Order By: Relevance
“…Nonetheless, the approach we took has some substantial limitations. Although multiple, strong lines of evidence indicate that the brief-waveform striatal neurons are FSIs (discussed in Berke et al, 2004;Mallet et al, 2005), this identification cannot be made with certainty using extracellular recording alone. We cannot readily establish whether the observed activity changes were the cause of altered behavior, or merely a correlate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the approach we took has some substantial limitations. Although multiple, strong lines of evidence indicate that the brief-waveform striatal neurons are FSIs (discussed in Berke et al, 2004;Mallet et al, 2005), this identification cannot be made with certainty using extracellular recording alone. We cannot readily establish whether the observed activity changes were the cause of altered behavior, or merely a correlate.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous studies using other data sets (Berke, 2008;Berke et al, 2004;Gage et al, 2008), we found clearly separate groups of striatal neurons (Figure 1a and b). The group with extremely brief waveforms was presumed to be PV + FSIs, on the basis of the brief waveforms of such cells in previous in vitro and anesthetized in vivo studies (Kawaguchi, 1993;Mallet et al, 2005), and the known intrastriatal distribution and firing patterns of FSIs (discussed in Berke et al, 2004). The large group of cells with longer-duration waveforms was presumed to be MSNs; these cells typically had much lower mean firing rates (in no case 410 Hz) and were not tonically active (not shown).…”
Section: Striatal Cell Classes and Recording Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, axons from each area synapse onto single fast spiking GABAergic interneurons. Interestingly, these interneurons are more responsive to cortical input than the medium spiny cells (Charpier et al, 1999;Mallet et al, 2005;Ramanathan et al, 2002;Takada et al, 1998). This suggests a potentially critical role for interneurons to integrate information from different cortical areas before passing that information onto the medium spiny projection cells.…”
Section: Connections Of the Vsmentioning
confidence: 96%
“…Two of the most examined sources of GABAergic inhibition into MSNs are the feedback inhibition (FB) from the axon collaterals of the MSNs themselves, and the feedforward inhibition (FF) via the small population (1-2% of striatal neurons) of fastspiking interneurons (FSIs) [25][26][27][28]. While feedback inhibition is made up of many weak inputs the feedforward inhibition is powerful, and spiking in a single FSI is capable of significantly delaying spike generation in a large number of postsynaptic medium spiny neurons [29][30][31][32][33][34]. High firing rate and uncorrelated spiking of FSIs may further amplify the effect of feedforward inhibition on the MSNs [35][36].…”
Section: Introductionmentioning
confidence: 99%